Enhancing attention in neurodegenerative diseases: current therapies and future directions - Sharma Kanchan (De Gruyter, 2016)
We all experience at least occasional lapses in attention but in some neurological conditions, loss of attention is pervasive and debilitating. Treating deficits in attention first requires an understanding of the neurobiology of attention, which we now understand to be a set of different cognitive processes. Cholinesterase inhibitors are already established as effective attentional enhancers used in the treatment of certain dementias. Other stimulant agents such as modafanil, amphetamine and methylphenidate have demonstrated limited success in healthy individuals where attention is already optimal and clinical trials in patients with neurological disease are sparse. Dietary and lifestyle changes are gaining increasing prominence, as are experimental treatments such as deep brain stimulation and transcranial magnetic stimulation. As the therapeutic arsenal widens, clinicians will be able to match specific treatments to selective deficits in attention, giving patients a tailored management plan. Here we review common diseases that impair attention and emphasise how an understanding of attentional processing within the brain might lead to improved therapeutic strategies.